DEVELOPMENT OF THE MECHANISM FOR FORMING ACADEMIC MOBILITY OF STUDENTS - Usarboyeva D. U. (Galaxy International Interdisciplinary Research Journal, 2024)
The article reflects on the principles, methods and pedagogical conditions of mobility in the pedagogical process by forming the rules of academic mobility among students and gives recommendations.